O combate ao tráfico internacional de bens culturais - Ana Luíza Fernandes Tótola (2018)
In the last decades, the protection of the cultural patrimony has intensified in the international, regional and also at domestic level. Notwithstanding the efforts made in this regard, the international traffic in cultural goods is a reality that reaches States around the world, handling huge profits every year. Concern has increased as the association of trafficking with other types of crime, such as terrorism, money laundering, corruption, other forms of trafficking, and the practice of such crime in the context of transnational organized crime has been noted. Analyzing the Brazilian legal system, it was verified that it is not completely in compliance with what is required of the Brazilian State taking into account the main international obligations with regard to combating illicit trafficking in cultural goods. Therefore, in the end, recommendations were made so that the domestic rules that refer to the issue are adequate to such obligations.